2013
DOI: 10.1093/cvr/cvt256
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidasin-like protein: a novel peroxidase homologue in the human heart

Abstract: PXDNL is a unique component of the heart with a recently evolved inactivation of peroxidase function. The elevation of PXDNL levels in the failing heart may contribute to ECM dysregulation due to its antagonism of PXDN function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…An inability to rescue pxn-2 mutant phenotypes may be a consequence of antagonistic roles for pxn-1 and pxn-2 , or of a differentiation of their roles temporally and/or spatially. A recent study on peroxidasins and peroxidasin-like proteins showed that human vascular peroxidasins are expressed in heart, and are putatively down-regulated by peroxidasin-like proteins ( Peterfi et al, 2014 ). The peroxidasin-like protein consists of a peroxidase domain lacking the crucial enzyme activity and cell adhesion domains, such as leucine-rich repeats (LRRs) and immunoglobulin (Ig) domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An inability to rescue pxn-2 mutant phenotypes may be a consequence of antagonistic roles for pxn-1 and pxn-2 , or of a differentiation of their roles temporally and/or spatially. A recent study on peroxidasins and peroxidasin-like proteins showed that human vascular peroxidasins are expressed in heart, and are putatively down-regulated by peroxidasin-like proteins ( Peterfi et al, 2014 ). The peroxidasin-like protein consists of a peroxidase domain lacking the crucial enzyme activity and cell adhesion domains, such as leucine-rich repeats (LRRs) and immunoglobulin (Ig) domains.…”
Section: Resultsmentioning
confidence: 99%
“…The peroxidasin-like protein consists of a peroxidase domain lacking the crucial enzyme activity and cell adhesion domains, such as leucine-rich repeats (LRRs) and immunoglobulin (Ig) domains. Hence, it is suggested that peroxidasin and peroxidasin-like protein can form complexes to inhibit the peroxidase activity of peroxidasin for proper regulation ( Peterfi et al, 2014 ). The relationship between pxn-1 and pxn-2 in C. elegans may be similar to this interaction between peroxidasin and peroxidasin-like protein in the human heart.…”
Section: Resultsmentioning
confidence: 99%
“…A peroxidasin-like protein (PXDNL) was recently identified in humans (3), however this protein lacks measurable peroxidase activity. Animal heme peroxidases (MPO, EPX and LPO) serve in the first line of host defense, while TPO has a crucial role in thyroid hormone synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…PXDN, a member of the larger peroxidase gene family, is an adhesion molecule involved in ECM formation (Peterfi et al 2014;Tauber et al 2010). It is one of the target genes of miR-29a.…”
Section: Relationship Between Genes' Expression and Survival In Primamentioning
confidence: 99%